Arthroscopic discopexy technique with anchors for treatment of temporomandibular joint internal derangement: Clinical and magnetic resonance imaging evaluation - Loureiro Sato, Fábio Ricardo [UNESP]; Tralli, Gustavo (Elsevier, 2020)
Purpose: The objective of this study was to describe a technique of arthroscopic discopexy with anchors used to treat temporomandibular joint internal derangement. Materials and methods: This study involved patients with unilateral temporomandibular dysfunction refractory to conservative treatment, and whose magnetic resonance imaging (MRI) examinations showed internal derangement of the temporomandibular disc, with anterior disc displacement. Maximal interincisal opening (MIO), joint pain, joint noise, and disc position were the variables assessed by clinical examination and MRI before and 6 months after the surgery. Results: The sample consisted of 20 patients. In the postoperative evaluation, MIO had increased from 33.8 ± 4.83 mm to 35.1 ± 4.08 mm (p = 0.04), while joint pain had decreased from 7.5 ± 1.42 points to 2.05 ± 1.47 points (p = 0.001). With regard to joint noise, 19 of the patients had presented with clicking or crepitation but after 6 months these were completely absent. Disc repositioning was complete in 15 of the patients and partial in the other five. Conclusion: The technique of arthroscopic discopexy with anchors was shown to be effective in treating temporomandibular internal derangement, with good clinical results.
Keywords: Arthroscopy; Temporomandibular disorder; Temporomandibular joint